A pre-relaxed FBG accelerometer using transverse forces with high sensitivity and improved resonant frequency - Li, Yuqing; Li, Kuo; Liu, Guoyong; Tian, Juan; Wang, Yanchun (Photonics Letters of Poland, 2020)
Fiber Bragg grating (FBG) accelerometers using transverse forces have higher sensitivity but lower resonant frequency than ones using axial forces. By shortening the distance between the two fixed ends of the FBG, the resonant frequency can be improved without lowing the sensitivity. Here, a compact FBG accelerometer using transverse forces with a slightly pre-relaxed FBG and 25mm distance between the two fixed ends has been demonstrated with the crest-to-trough sensitivity 1.1nm/g at 5Hz and the resonant frequency 42Hz. It reveals that making the FBG slightly pre-relaxed rather than pre-stretched also improves the tradeoff between the sensitivity and resonant frequency. Full Text: PDF References: Kawasaki, B. S. , Hill, K. O , Johnson, D. C. , & Fujii, Y. , "Narrow-band Bragg reflectors in optical fibers", Optics Letters 3, 66 (1978) [CrossRef] K. O. Hill, and G. Meltz, "Fiber Bragg grating technology fundamentals and overview", Journal of Lightwave Technology 15, 1263 (1997) [CrossRef] B. Lee, "Review of the present status of optical fiber sensors", Optical Fiber Technology, 9, 57-79 (2003) [CrossRef] Laudati, A. , Mennella, F. , Giordano, M. , D"Altrui, G. , Tassini, C. C. , & Cusano, A., "A Fiber-Optic Bragg Grating Seismic Sensor", IEEE Photonics Technology Letters, 19, 1991 (2007) [CrossRef] P. F. Costa Antunes, C. A. Marques, H. Varum, and P. S. Andre, "Biaxial Optical Accelerometer and High-Angle Inclinometer With Temperature and Cross-Axis Insensitivity", IEEE Sens. J. 12, 2399 (2012) [CrossRef] Guo, Y. , Zhang, D. , Zhou, Z. , Xiong, L. , & Deng, X., "Welding-packaged accelerometer based on metal-coated FBG", Chinese Optics Letters, 11, 21 (2013). [CrossRef] Zhang, Y. , Zhang, W. , Zhang, Y. , Chen, L. , Yan, T. , & Wang, S. , et al., "2-D Medium–High Frequency Fiber Bragg Gratings Accelerometer", IEEE Sensors Journal, 17, 614(2017) [CrossRef] Xiu-bin Zhu, "A novel FBG velocimeter with wind speed and temperature synchronous measurement", Optoelectronics Letters, 14, 276-279 (2018) [CrossRef] Li, K. , Yau, M. H. , Chan, T. H. T. , Thambiratnam, D., "Fiber Bragg grating strain modulation based on nonlinear string transverse-force amplifier", & Tam, H. Y. , Optics Letters, 38, 311 (2013) [CrossRef] Li, K. , Chan, T. H. T. , Yau, M. H. , Nguyen, T. , Thambiratnam, D. P. , & Tam, H. Y., "Very sensitive fiber Bragg grating accelerometer using transverse forces with an easy over-range protection and low cross axial sensitivity", Applied Optics, 52, 6401 (2013) [CrossRef] Li, K. , Chan, T. H. T. , Yau, M. H. , Thambiratnam, D. P. , & Tam, H. Y., "Biaxial Fiber Bragg Grating Accelerometer Using Axial and Transverse Forces", IEEE Photonics Technology Letters, 26, 1549 (2014). [CrossRef] Li, K. , Chan, T. H. , Yau, M. H. , Thambiratnam, D. P. , & Tam, H. Y., "Experimental verification of the modified spring-mass theory of fiber Bragg grating accelerometers using transverse forces", Applied Optics, 53, 1200-1211(2014) [CrossRef]